Շարահյուսական որոշ զուգաբանությունների արտահայտությունը բարբառային հայերենում - Կատվալյան, Վիկտոր; Խառատյան, Մելանյա; Սահակյան, Նինա (ՀՀ ԳԱԱ ԼԻ հրատ.)
The article presents territorial manifestations of about ten syntactic isoglosses in dialectal Armenian. They are observed in more than 130 speeches, representing all dialect groups of the Armenian language. IIsoglosses refer to both the order and agreement of sentence members, as well as their expression and formation. It is noticeable that both dialect groups and dialects and speeches can differ in syntactic features. They also determine the relationship between dialect units. Like other dialectal features, syntactic features also vary in prevalence: in addition to those that are widely spread, there are also those that have a rather limited scope. In the article, a number of new syntactic isoglosses are formulated, which can also be included in the field of studying dialectal realities. В статье представлены территориальные проявления около десяти синтаксических изоглосс в диалектном армянском языке. Они наблюдаются более чем в 130 говорах, представляющих все диалектные группы армянского языка. Изоглоссы относятся как к порядку и согласованию членов предложения, так и к их выражению и формированию. Заметно, что как диалектные группы, так и диалекты и говоры могут различаться по синтаксическим особенностям. Они также определяют взаимоотношения между диалектными единицами. Как и другие диалектные признаки, синтаксические признаки также различаются по распространенности: рядом с теми, у кого большое распространение, могут быть те, у которых охват довольно ограничен. В работе сформулирован ряд новых синтаксических изоглосс, которые также могут быть включены в область изучения диалектных реалий.
Keywords: Բարբառագիտություն